Digital Humanities and Cultural Preservation - Meisuri Meisuri (Penelitian dan Pengembangan Ilmu, 2024)
This research aims to investigate how digital humanities can help overcome bias and discrimination in cultural representation. The research method used is a systematic literature review, where various articles, journals and scientific publications related to the theme are systematically investigated. The research results show that digital humanities has great potential in reducing bias and discrimination in cultural representation through a variety of approaches, including the use of technology to re-engineer cultural narratives, digital data analysis to identify and reduce bias in datasets, and the provision of inclusive digital education to expand coverage. accurate cultural representation. This study concludes that digital humanities has a crucial role in improving cultural representation that is more diverse and inclusive, but challenges such as limited resources and rapid technological developments still need to be overcome to maximize the potential of digital humanities in overcoming bias and discrimination in cultural representation.